Some Aspects of Housing in Slovenia - Andrej Božin; Blaž Grudnik Tominc (Naše gospodarstvo/Our economy, 2012)
The supply side of the housing policy in society is inherently associated with construction. In Slovenia, construction peaked in 2008, but the economic crisis affected construction more than other industries. Construction works, including maintaining and living in buil- dings, contribute significantly to environmental pressures. In accordance to EU directives, Slovenia’s national plan of energy performance for 2008–2016 includes two main objectives: encouraging improvements of the energy performance of buildings and technologi- cal development regarding materials, technologies regarding energy, etc. In Slovenia, the important characteristic regarding tenure types is that the ownership rate is very high. This may have several negative impacts on mobility, which is lower among owner-occupants, as well as implications for the functioning of the labour market. The process of housing acquisition may include many difficulties caused by problems at the supply or the demand side. The housing policy on the supply side should be focused on ensuring relevant housing conditions, while on the demand side it should be based on a treatment of those house- holds entitled to help in this process. Housing-related policies must achieve their objectives in an efficient and equitable way. The deepening economic crisis in Slovenia makes this task very complex. The housing market policy in Slovenia has been criticised since the establishment of the Housing Fund of the Republic of Slovenia as its actions primarily targeted the strengthening of the demand side, thereby affecting the high prices of housing in Slovenia in the past. The equilibrium of the demand and supply side of housing with sustainable and energy-efficient construction and building should be the goal of an efficient housing policy. As a possible solution, we suggest cooperation among municipalities, European structural funds, and national funds, all together aimed at sustainable and energy-efficient housing solutions.